2022
DOI: 10.1002/chem.202200874
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonalization of Polyaryl Linkers as a Route to More Porous Phosphonate Metal‐Organic Frameworks

Abstract: The coordinative pliancy of the phosphonate functional group means that metal-phosphonate materials often self-assemble as well-packed structures with minimal porosity, as efficient inter-ligand packing is enabled. Here, we report a multistep synthesis of a novel aryl-phosphonate linker with an orthogonalized ligand core, 1,3,5-tris(4'-phosphonophenyl)-2,4,6-trimethylbenzene (H 6 L2) designed to form more open structures. A series of crystalline metal-phosphonate frameworks (CALF-35 to -39) have been assembled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…This finding indicates that the aromatic cores of the OP1 ligand strongly contributes to the stabilization of CO 2 in CALF‐37, whereas the stabilization of N 2 is minor. This agrees with the high selectivity of CALF‐37 toward CO 2 over N 2 , observed experimentally [16] . In the PP region, the interactions consist of a subtle interplay between electrostatic and LJ, which depends on the distance between the adsorbate (CO 2 or N 2 ) and the ligands.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…This finding indicates that the aromatic cores of the OP1 ligand strongly contributes to the stabilization of CO 2 in CALF‐37, whereas the stabilization of N 2 is minor. This agrees with the high selectivity of CALF‐37 toward CO 2 over N 2 , observed experimentally [16] . In the PP region, the interactions consist of a subtle interplay between electrostatic and LJ, which depends on the distance between the adsorbate (CO 2 or N 2 ) and the ligands.…”
Section: Resultssupporting
confidence: 88%
“…It's counter‐intuitive that the CO 2 molecules cannot diffuse between the pores, since the CO 2 molecules are expected to diffuse across the network in order to be adsorbed. Like the diffusion of water molecules during the activation, our CO 2 diffusion calculation can indicate that the adsorption of CO 2 in CALF‐37 is a very slow process, as observed during the adsorption isotherms measurements [16] . As a matter of fact, the authors revealed that 2–3 days were necessary for the maximum CO 2 uptake with CALF‐37, which confirmed the relatively slow kinetics of the process when compared to the other CALFs.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations